Infodemic mechanism based on the SIR model: a population mobility perspective - Li, Cun Lin (Politechnica University of Bucharest, 2023)
Ease of access and transmission of information through social media has led to ambiguity, the scope of misinformation, and uncertainty, especially during the time of public health emergencies when there is a huge demand for health information due to the lack of scientific knowledge of health knowledge among online users. Inaccurate health information will induce social disorders such as panic during the epidemic Covid-19 outbreak, which has drawn increasing attention from scholars and the government. The purpose of the study is to construct a dynamic misinformation fading model by initially considering the population mobility possibility based on the classic SIR model, thus making the infordemic spreading process more realistic and apparent. The proposed model helps to understand the impact of misinformation online by deriving and simu-lating the important parameters: misinformation-free equilibrium, spreading duration, and the social stability index to revealing the misinformation development trend. Fi-nally, the research identifies more efficient measures that could be employed in times of government officials or companies during public health emergencies.